Properties of particleboards made from Acacia seyal var. using UF-tannin modified adhesives - Elbadawi, M.; Osman, Z.; Md. Tahir, Paridah; Nasroun, T.; Kantiner, W. (Editura Academiei Romane, 2015)
The aim of this study was to investigate the effect of adding a blend of tannins to commercial urea formaldehyde (UF) on the properties of particleboard made from wood particles of Acacia seyal var. seyal. The tannins were extracted from the bark of Acacia seyal var. seyal (Ass) and Acacia nilotica subsp. tomentosa (Ant) with hot water (initial temperature was 90 ºC), using a ratio of powdered b ark to water of 1:6 (w/v). The tested Acacia specie s (Ass and Ant) exhibited high tannin contents (82.18% and 73.09%, respectively). A blend from the two tannin types (B T) was made (1:1 w/w) and added to UF in the form of a concentrated solution (35%) at three different percentages (5%, 10% and 15%, weight/weight). The different UF–BT formulations were used to produce particleboards (340 mm × 340 mm × 10 mm in size). The obtained panels were tested according to the BSEN relevant standards and showed high mechanical properties, compared to the ones produced by solely UF. It was also observed that the addition of BT to UF did not improve the physical properties of the panels (thickness swelling (TS) and water absorption (WA)), but the results obtained were slightly higher than the ones for the UF panels.